Synthesis, Characterization and Biological Evaluation of Some New Pyrazoline Derivatives - Kumar Jain, Dinesh; Bhadoriya, Upendra; Lal Lodhi, Jawahar (Asian Journal of Chemistry, 2012)
Pyrazoline derivatives have been found to possess appreciable antitubercular activity against Mycobacterium tuberculosis. The present study aimed to synthesize some potent antitubercular pyrazoline derivatives. Different substituted pyrazoline derivatives were synthesized by cyclization of substituted chalcone derivatives in presence of hydrazine hydrate. Synthesized derivative were characterized by melting point, TLC, FT-IR, 1H NMR and MS spectrometry. Synthesized derivatives were evaluated for their in vitro antitubercular activity against M. tuberculosis. Derivatives JA1, JA2, JA3 and JA5 were found to be most potent and showed greater zone of inhibition than control which is comparable to standard drug rifampicin.